Pengaruh Affiliate Marketing Terhadap Purchase Decision Melalui Buying Interest : Studi pada Konsumen Produk Skintific - Isymayati Ash Shiddiqy; Fian Arifiona Faradila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of affiliate marketing on purchase decisions through buying interest in Skintific skincare products at the Skintific Shopee Affiliate Official Store. The research consists of one independent variable, namely affiliate marketing, and one dependent variable, namely purchase decision and buying interest as intervening variables. The method used is path analysis. The data collection method uses a questionnaire with purposive sampling technique. The number of respondents obtained was 100 people, this number was obtained based on the Roa Purba formula. The research results obtained based on the Partial Test showed: 1) there is a significant influence of affiliate marketing on buying interest, 2) there is a significant influence of affiliate marketing on purchase decisions, 3) there is a significant influence of buying interest on purchase decisions, 4) buying interest can mediate the influence of affiliates marketing on purchase decisions.